Synthesis and characterization of graphite-encapsulated iron nanoparticles from ball milling-assisted low-pressure chemical vapor deposition. (November 2017) - Ağaoğulları, Duygu; Madsen, Steven J.; Ögüt, Burcu; Koh, Ai Leen; Sinclair, Robert
Abstract: Graphite-encapsulated Fe nanoparticles were synthesized using a combined method of high-energy ball milling and low-pressure chemical vapor deposition (LPCVD). Fe2 O3 and graphite powders were milled to increase their surface areas and obtain a more homogeneous distribution. LPCVD was performed at a pressure of ∼0.57 Torr in a tube furnace under a CH4 /H2 atmosphere at 1050 °C for 1 and 3 h. As-synthesized samples were purified in a 2 M HF solution. Characterization was performed using X-ray diffractometry (XRD), scanning and transmission electron microscopy (SEM and TEM) and alternating gradient magnetometry (AGM). XRD revealed the presence of body centered cubic (BCC) and face centered cubic (FCC) Fe phases without residual iron oxides. SEM confirmed the powders were better mixed and smaller after ball milling compared to mortar and pestle milled powders. High resolution TEM showed all nanoparticles had at least four and on average 16 graphitic layers, around an Fe core ranging from 20 to 300 nm. Magnetic measurements indicated that nanoparticles exhibit soft ferromagnetic behavior with low saturation magnetization (17–21 emu/g) and coercivity (110 Oe). A chemical stability test performed in a 2 M HCl solution showed that graphitic shells did not degrade, nor was there evidence of core dissolution or shell discontinuity. Graphical abstract: